PECULIARITIES OF GEOCHEMICAL MIGRATION OF ELEMENTS AND COMPOUNDS IN NATURAL AND NATURAL-ANTHROPOGENIC COMPLEXES OF RIVER LOPAN - ТІТЕНКО, Г. В.; КЛЄЩ, А. А. (Man and Environment. Issues of Neoecology, 1970)
It was determined that the soil cover of the river valley is characterized by a significant transformation of basic chemical, physical-chemical properties of soil and humus condition that affects the main areas and the intensity of the geochemical migration of chemical elements. In the river valley Lopan there are signs formation of a new man-made physical-chemical alkaline geochemical barrier in superaqual and eluvial-accumulative landscapes (floodplain and floodplain terraces r.Lopan), which contributes to the intensification of surface accumulation of chemical elements and braking processes of vertical and horizontal migration. It is established that the most of the investigated valley alkalinization urban soil surface layer reduces the migration ability of various contaminants, including heavy metals.